2019
DOI: 10.1111/joes.12340
|View full text |Cite
|
Sign up to set email alerts
|

Taxation of Economic Rents

Abstract: Economic rents have long been identified as an efficient tax base. In addition, the recent literature documents that rent income is highly concentrated and that rents are quickly increasing. Rent taxation thus seems attractive for reasons of both efficiency and equity. Nevertheless, rent taxation remains a marginal topic in research and policy making. In a systematic review of the neoclassical literature on different rent types, we find that some types of rents reflect inefficiencies and should thus be minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 151 publications
(200 reference statements)
0
16
0
Order By: Relevance
“…Further, in Section 5, we analyzed the effects of three kinds of taxes and showed that the growth rate will increase even if the tax revenue is wasted. Particularly, these outcomes indicate that the government could use the tax revenue to finance other useful expenditures, such as environmental protection (Dao and Edenhofer 2018;, reduction in income and wealth inequality (Koethenbuerger and Poutvaara 2009;Schwerhoff et al 2020) or public infrastructure (Bosi and Pham 2016). Additionally, in our model, the whole tax incidence falls to the landowners because the marginal productivity of capital remains constant.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Further, in Section 5, we analyzed the effects of three kinds of taxes and showed that the growth rate will increase even if the tax revenue is wasted. Particularly, these outcomes indicate that the government could use the tax revenue to finance other useful expenditures, such as environmental protection (Dao and Edenhofer 2018;, reduction in income and wealth inequality (Koethenbuerger and Poutvaara 2009;Schwerhoff et al 2020) or public infrastructure (Bosi and Pham 2016). Additionally, in our model, the whole tax incidence falls to the landowners because the marginal productivity of capital remains constant.…”
Section: Discussionmentioning
confidence: 86%
“…In this setting, growth will only be spurred if the land tax substitutes an existing distortionary tax. In a recent paper, Schwerhoff et al (2020) provided a survey on the taxation of economic rents and economic inequality. They provided reasoning as to why the taxation of rents is an appropriate policy measure to reduce inequality without creating deadweight losses.…”
Section: Literature Review: Land Taxationmentioning
confidence: 99%
“…Except for the PSC and SC that are forms of contractual systems, the other arrangements are forms of the concessionary systems. Regardless of the system in place, the crux is on how to recover costs and share the profit, which is the "Economic Rent": the difference between the value of production and the cost of extraction (Schwab and Werker, 2018;Schwerhoff et al, 2019).…”
Section: Fiscal Regime Elementsmentioning
confidence: 99%
“…Scope of practical use of research results: the research results can be used in developing strategies and programs of Ukrainian economy' innovative diversification in the process of its further competitive integration into the global economic space, that, among other things, requires the creation of conditions for improving the rent-generating properties of workforce and social environment, as well as increasing the level of its capitalization. example, to the rational selection of personnel and organization of its work, optimization of managerial, technological, financial and marketing processes, involvement of other factors related to the reproductive application of human intelligence [4][5][6][7], as well as to the use of various quasi-competitive advantages stimulating the growth in demand for the corresponding goods and services.…”
Section: Description Of the Problemmentioning
confidence: 99%